Upaya Reduksi Searching Time Pada Area Gudang Penyimpanan Barang di PT LBP Dengan Metode 5S - Candra Setya Nugraha; Rizqi Novita Sari (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
PT LBP is a manufacturing company that provides products and services, especially specialists in the field of industrial tanks. The products made are dominated by products that function to support production processes in industry, for example Storage Tanks, Pressure Tanks, Silos, Heat Exchangers, and so on. In carrying out its work, PT LBP has a warehouse as a place to store goods, which is an area that functions to store goods or components and makes a very important contribution to the speed of a project. Currently, PT LBP still uses conventional methods in its goods storage system. There is still haphazard storage, there are no procedures for grouping types of goods, such as grouping types of high frequency goods and the like. Items included in the high frequency category are 4 inch grinding stones, 4 inch cutting stones, P80 plasma nozzles, welding wire and welding filler. This causes an irregular buildup of goods or components and even blocks the process of entering and exiting the road. Therefore, the 5S method is very suitable if applied to PT LBP, the 5S method will improve the system for structuring, sorting, cleaning and storing goods with the aim of reducing searching time for inventory in the warehouse storage area. The results of the design carried out were rearranging the placement of goods, cleaning goods, and implementing procedures in accordance with the 5S concept.